2019
DOI: 10.3390/min9050274
|View full text |Cite
|
Sign up to set email alerts
|

Consideration of Influential Factors on Bioleaching of Gold Ore Using Iodide-Oxidizing Bacteria

Abstract: Iodide-oxidizing bacteria (IOB) oxidize iodide into iodine and triiodide which can be utilized for gold dissolution. IOB can be therefore useful for gold leaching. This study examined the impact of incubation conditions such as concentration of the nutrient and iodide, initial bacterial cell number, incubation temperature, and shaking condition on the performance of the gold dissolution through the experiments incubating IOB in the culture medium containing the marine broth, potassium iodide and gold ore. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…A comparison of maximum bioleaching yields achieved in this study and selected previous studies is shown in Table 7 . The maximum gold yield detected for R. tolerans with gold concentrate in this study was similar to that reported by Khaing et al [ 14 , 21 ] for other R. tolerans strains leaching sulfide ore. However, the maximum yield obtained with R. mucosus for ore concentrate was lower than that previously reported for strains of Roseovarius genus.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…A comparison of maximum bioleaching yields achieved in this study and selected previous studies is shown in Table 7 . The maximum gold yield detected for R. tolerans with gold concentrate in this study was similar to that reported by Khaing et al [ 14 , 21 ] for other R. tolerans strains leaching sulfide ore. However, the maximum yield obtained with R. mucosus for ore concentrate was lower than that previously reported for strains of Roseovarius genus.…”
Section: Discussionsupporting
confidence: 91%
“…The application of IOB for bioleaching gold has been previously proposed as a sustainable alternative to cyanide [ 10 ] and, the use of IOB isolated from iodide-rich brine waters has been explored for leaching gold from gold-containing ore [ 14 , 21 ]. This study evaluated the ability of IOB sourced from a commercial culture collection, R. tolerans DSM 11457 T and R. mucosus DSM 17069 T , to bioleach gold from e-waste and sulfidic gold ore concentrate.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations